EYESCHATCHER Assisted by SWISHMAX as an Alternative Learning Media for Millennial Generation - samsiya samsiya; Fury Styo Siskawati (Universitas Islam Jember, 2020)
The aim of this research to develop alternative learning media that comfort for milenial generation. This media is given name of eyeschatcher; it is making with swishmax application. This research was done in SMPN 01 PAKUSARI with the data colleting methode are interview, observation, documentation, test and questioner. And than the development model that used is ASSURE that consists of six stages, including analyzing students, stating objectives, choosing methods, media, and materials, utilizing media and materials, requiring student participation, evaluating and reviewing. Based on the stages that have been carried out it can be explained that the entire stages have been passed and can be said successfully developed eyeschatcher assisted by swishmax as an alternative learning media for millennial generation Keywords: eyeschatcher, swishmax, millennial generation